PENGARUH LEMBAR KERJA PESERTA DIDIK (LKPD) TERINTEGRASI MATERI TSUNAMI TERHADAP KOMPETENSI FISIKA DALAM PEMBELAJARAN REASONING AND PROBLEM SOLVING PADA MATERI GETARAN HARMONIK, IMPULS DAN MOMENTUM DI KELAS XI SMAN 10 PADANG - Elsa Listia; Asrul Asrul; Ahmad Fauzi (Universitas Negeri Padang, 2016)
Low competence of physics of students was due to the lack of motivation and lack of ability in problem solving. It could be solved by integrating tsunami matterial in Reasoning and Problem Solving learning. The purposs of these research was to investigate the effect and contribution of integrating tsunami matterial, and the effect of Reasoning and Problem Solving model towards cognitive competence of physics. This was a Quasi Experiment research with population was all of students of class XI MIA SMAN 10 Padang enrolled in the academic year 2015/2016. The result of reserch showed that there was difference between learning outcome of experiment class and control class on affective, cognitive, psikomotor and learning out come of cognitive before and after using Reasoning and problem solving model. Through t test, tcount was beyond acceptance of Ho. By using Regression and correlation test, it was obtained that the contribution of integrating tsunami material towards affective was 48,89%, 51,27% towards cognitive, and 56,88% towards psikomotor. The average of learning outcome on cognitive before and after using Reasoning and Problem Solving showed improvement. By using t test, t count was beyond acceptance of Ho. The conclusions of these research are hypothesis which stated: 1) There was effect of integrating tsunami material towards physics competence at the real level of 0,05 could be accepted, 2) the contribution of Integrating tsunami material towards physics competence was strong, 3) There was effect of Reasoning and Problem Solving model towards cognitive competence of physics at the real level of 0,05 could be accepted